2020
DOI: 10.3389/fmicb.2020.00151
|View full text |Cite
|
Sign up to set email alerts
|

The Epipeptide YydF Intrinsically Triggers the Cell Envelope Stress Response of Bacillus subtilis and Causes Severe Membrane Perturbations

Abstract: The Gram-positive model organism and soil bacterium Bacillus subtilis naturally produces a variety of antimicrobial peptides (AMPs), including the ribosomally synthesized and post-translationally modified AMP YydF, which is encoded in the yydFGHIJ locus. The yydF gene encodes the pre-pro-peptide, which is, in a unique manner, initially modified at two amino acid positions by the radical SAM epimerase YydG. Subsequently, the membrane-anchored putative protease YydH is thought to cleave and release the mature AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 73 publications
0
61
0
Order By: Relevance
“…B. subtilis PspA is regulated by σ W ( Wiegert et al, 2001 ; Cao et al, 2002a ), whereas the paralog LiaH is regulated by the LiaRS TCS ( Mascher et al, 2004 ; Jordan et al, 2006 ). Both paralogs localize to the membrane in response to stress and protect against membrane-damaging antibiotics ( Wolf et al, 2010 ; Kingston et al, 2013 ; Dominguez-Escobar et al, 2014 ; Popp et al, 2020 ). In the case of LiaH, membrane association is mediated by interaction with the integral membrane protein LiaI ( Dominguez-Escobar et al, 2014 ).…”
Section: Cell Envelope Stress Responses That Function Through Membrane Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…B. subtilis PspA is regulated by σ W ( Wiegert et al, 2001 ; Cao et al, 2002a ), whereas the paralog LiaH is regulated by the LiaRS TCS ( Mascher et al, 2004 ; Jordan et al, 2006 ). Both paralogs localize to the membrane in response to stress and protect against membrane-damaging antibiotics ( Wolf et al, 2010 ; Kingston et al, 2013 ; Dominguez-Escobar et al, 2014 ; Popp et al, 2020 ). In the case of LiaH, membrane association is mediated by interaction with the integral membrane protein LiaI ( Dominguez-Escobar et al, 2014 ).…”
Section: Cell Envelope Stress Responses That Function Through Membrane Proteinsmentioning
confidence: 99%
“…Subsequent studies revealed that YydF is post-translationally processed to convert two L-amino acids to D-amino acids ( Benjdia et al, 2017 ). The resulting epipeptide, YydF ∗ , induces LiaRS-regulated LiaH and the FloT flotillin ( Popp et al, 2020 ). The modified YydF ∗ peptide kills B. subtilis cells by dissipating the membrane potential via membrane permeabilization.…”
Section: Cell Envelope Stress Responses That Function Through Membrane Proteinsmentioning
confidence: 99%
“…After treatment, cells were transferred to 50 ml falcons and growth was immediately stopped in an ice water bath followed by centrifugation at 8000 rpm at 4 • C for 3 min. The supernatants were discarded, and the resulting pellets were stored at −80 • C. RNA isolation was performed with a phenol-chloroform extraction method as previously described (Popp et al, 2020). The cDNA library was prepared using the NEB Ultra RNA directional prep kit for Illumina and sequencing was performed on an Illumina HiSeq3000 system.…”
Section: Rna Sample Preparation and Sequencingmentioning
confidence: 99%
“…We observed a slight growth inhibition of C. thermocellum in the presence of myo -inositol, however this required a high concentration (1 mg/mL) of myo -inositol ( Figure S2 ). YydF is predicted to be an exported and modified peptide that has antimicrobial and/or signaling properties [ 49 , 50 ]. YxaL, which contains a repeated pyrrolo-quinoline quinone (PQQ) domain that forms a beta-propeller structure, interacts with the DNA helicase PcrA in B. subtilis [ 51 ].…”
Section: Resultsmentioning
confidence: 99%